THE RIGHT TO SUSPEND PERFORMANCE IN THE CASE OF ANTICIPATORY BREACH OF CONTRACT ON INTERNATIONAL SALE OF GOODS - Zdravkovic, Uros (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Article 71 of the CISG authorizes a seller or a buyer to suspend performance of its obligations under the sales contract if the party is unlikely to receive a substantial part of the counter-performance promised by the other party. The suspending party does not breach the contract if the suspension is rightful. If, however, the suspension is not authorized by article 71, the suspending party will breach the contract when it fails to perform its obligations.A party may suspend the performance of his obligations if, after the conclusion of the contract, it becomes apparent that the other party will not perform a substantial part of his obligations as a result of a serious deficiency in his ability to perform or in his creditworthiness or his conduct in preparing to perform or in performing the contract.The right to suspend under article 71 is to be distinguished from the right to avoid the contract. Unlike avoidance of the contract, which terminates the obligations of the parties, the suspension of contractual obligations recognizes that the contract continues and encourages mutual reassurance that both parties will perform.If the seller has already dispatched the goods, he may prevent the handing over of the goods to the buyer even though the buyer holds a document which entitles him to obtain them. This relates only to the rights in the goods as between the buyer and the seller.A party suspending performance, whether before or after dispatch of the goods, must immediately give notice of the suspension to the other party and must continue with performance if the other party provides adequate assurance of his performance.
Keywords: The law on international sale of goods; CISG; anticipatory breach of contract; suspension of performance